Pelatihan Keterampilan Dasar Membaca Teks Berbahasa Inggris bagi Siswa SMKSI Darul Istiqomah Jember - Agus Setia Budi; Cholimatus Zuhro; Nila Susanti; Alfi Hidayatu Miqawati; Fitri Wijayanti (Aksi Nyata : Jurnal Pengabdian Sosial dan Kemanusiaan, 2025)
English reading skill is a fundamental skill that is crucial in education, particularly in today's globalized world. However, many Vocational High School (SMK) students still face challenges in comprehending English texts, stemming from limited vocabulary, limited reading strategies, and a lack of contextual learning. This community service activity was conducted at SMK Swasta Islam (SMKSI) Darul Istiqomah Jember to provide students with basic English reading skill training. The training focused on mastering reading strategies such as skimming, scanning, determining topics, identifying main and supporting ideas, and answering questions using WH-Questions. The implementation method included initial observation, material preparation, interactive lectures, practice exercises, and evaluation. The results showed that the training successfully improved students' ability to comprehend English texts more effectively and efficiently. Furthermore, it increased students' motivation and confidence in reading English texts, and provided an initial understanding of functional texts relevant to the world of work. This activity is expected to be a real contribution in improving the quality of vocational high school students' English literacy and supporting their readiness to face the demands of the global workforce.